Sustainable entrepreneurial intention: A research trends and agenda - Alejandro Valencia-Arias; Lucía Palacios-Moya; Wilmer Londoño-Celis; Kathyusca Ipaguirre Sanchez (Sustainable Environment)
Interest in sustainable entrepreneurship has grown in both academic and business circles, with the aim of promoting the creation of environmentally and socially responsible enterprises. However, achieving true sustainability in entrepreneurship is fraught with complex challenges and dilemmas. The aim of this study is to examine research trends. The PRISMA-2020 methodology was used to analyse publications in the Scopus and Web of Science databases. The analysis included the examination of publications by year, main references, thematic evolution, keyword co-occurrence network, emerging and growing words. The results showed a remarkable growth of scientific literature in the years 2022 and 2023. The main research references include Wagner M. as well as journals such as Sustainability, and the influence of the United States, Pakistan, and Germany on scientific production. The thematic evolution showed a shift towards themes such as university support, sustainability, and environmental values. The main thematic clusters were characterised by the high conceptual affinity between terms such as Entrepreneurial Intention and Entrepreneurship. Emerging terms such as Circular Economy and Subjective Norms indicate a growing interest in specific aspects of sustainability. The text provides a strong basis for future research and the development of research agendas to address the identified gaps.